PELANGGARAN HUKUM HUMANITER INTERNASIONAL DALAM AGRESI ISRAEL TERHADAP PALESTINA TAHUN 2022 - Ahmad, S. Thoriq Musthofa; Susilowati, Ida; Munzilin, Khairul; Ardiyanti, Dwi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Israel and Palestine have been at war with one another for many years. Israel and Palestine believe they are entitled to the same area as a piece of the state's territory, so Israel keeps attacking Palestine. This research talks about Israel's aggression towards Palestine in 2022 and how those violations of international humanitarian law relate to that aggression. In armed conflict, humanitarian law has established mechanisms. In 2022, Israel engaged in several military operations in the Palestinian territory that cost the lives of troops and civilians.